Maintaining surgical skills for military general surgery: the potential role for multivisceral organ retrieval in military general surgery training and practice. Issue 4 (4th August 2015) - O'Reilly, David; Lordan, J; Streets, C; Midwinter, M; Mirza, D
Abstract : The closure of the Medical Treatment facility in Camp BASTION and the return to contingency operations presents a new challenge in training and maintaining the skills of military surgeons. Multivisceral organ retrieval presents a unique opportunity to practice some of the more unusual techniques required in military surgery in the National Health Service. This article details the experience that organ retrieval offers and matches this to the needs of military surgeons. National Organ Retrieval Service teams need skilled surgeons, and a mutually beneficial partnership is in prospect.